PENGEMBANGAN WELCOME DRINK BERBAHAN DASAR TEMULAWAK (Curcuma xanthorrhiza roxb) BERBASIS PEMODELAN MATEMATIKA DAN EKSPERIMEN - Randhi Nanang Darmawan; Kanom Kanom; Nurhalimah Nurhalimah (Universitas Muhammadiyah Semarang, 2021)
Welcome drink is an added value that enhances the Indonesian hospitality in the hotel industry, especially if it is made with spices such as curcuma, cinnamon, lemon, and brown sugar however industries that make typical curcuma beverage are often found to use excessive sugar and tend to turn off the distinctive taste of curcuma, besides that it also has an adverse effect on health.This research is an applied research which aims to make a beverage from curcuma and cinnamon with a mathematical approach at the end of the making process, a mathematical model can be simulated by numerical computation so that information on sugar levels are normal and reasonable for consumption in the welcome drink that has been made. Result of the research obtained 1st order homogeneous linear differential equation and simulation results using 40-80 gram sugar obtained a constant rate of change in sugar substances of or equivalent to 9-120 brix